Workshop Perhitungan Kebutuhan Ketenagaan Di Rumah Sakit - Danurjaya, Danurjaya; Solehudin, Solehudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hospital staffing is a concept that includes planning, management and development of human resources in the context of health service provision. Calculation of hospital personnel needs is an inevitable foundation for ensuring optimal and responsive health services. The aim of this community service is to socialize the calculation of staffing needs in hospitals. The implementation of community service was carried out in the hall of one of the private hospitals in the city of Bogor on 21 – 22 February 2024 at 08.30 – 16.00 WIB. The lecturers' community service activities were attended by 23 unit heads who came from several units in the hospital. Workshops create opportunities to build synergy among various teams and departments within the hospital. Strong collaboration between management, medical personnel, and administrative staff helps align efforts to achieve common goals. The availability of doctors, nurses and other professional health workers has a direct impact on a hospital's ability to provide good health services. The number and quality of health workers will influence the level of attention and care that can be given to patients.